Analisis Hak dalam Harta Berdasarkan Al-Qur’an dan Hadist, Sebagai Panduan Pengelolaan Aset - Megawati Kusuma Dewi, Trisia; Syukri Pulungan, Muhammad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The existence of wealth is very important to support the perfection of human life, facilitate meeting world needs and carrying out worship, both ritual and social, even one of the jihads must be with wealth. Therefore, Islam through the Qur'an and Hadith provides guidance regarding wealth, so that humans can position their assets correctly to achieve safety and happiness in this world and the hereafter. The purpose of writing this article is to look at several hadiths about property and the conflicting meanings of hadiths regarding the content of rights in property. The method used is a simple literature review method based on relevant reference sources. This article concludes that in the hadiths regarding wealth, in general it can be concluded that there is no conflict regarding how to obtain property. However, what shows that there is a conflict in meaning is the hadith regarding rights in property narrated by Ibn Majah and Imam al-Thabarani which is also found in the book al-Talkhish al-Habir by Ahmad ibn Ali Muhammad al-Kananiy al-Asyqalani. The wording that differentiates it is "There are no rights in assets other than zakat" and the wording "There are no rights in assets stored from zakat". The method used to understand this hadith is through the method of compromise and tracing the sanad so that its meaning can be understood.